Unconventional Policy Instruments in the New Keynesian Model - Alla, Zineddine; Espinoza, Raphael; Ghosh, Atish (Washington, D.C. : International Monetary Fund, 2016)
This paper analyzes the use of unconventional policy instruments in New Keynesian setups in which the 'divine coincidence' breaks down. The paper discusses the role of a second instrument and its coordination with conventional interest rate policy, and presents theoretical results on equilibrium determinacy, the inflation bias, the stabilization bias, and the optimal central banker's preferences when both instruments are available. We show that the use of an unconventional instrument can help reduce the zone of equilibrium indeterminacy and the volatility of the economy. However, in some circumstances, committing not to use the second instrument may be welfare improving (a result akin to Rogoff (1985a) example of counterproductive coordination). We further show that the optimal central banker should be both aggressive against inflation, and interventionist in using the unconventional policy instrument. As long as price setting depends on expectations about the future, there are gains from establishing credibility by using any instrument that affects these expectations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet